A Suitable Numerical Approximation for the Thermal Postbuckling Behaviour of Orthotropic Circular Plates - Nair, Anju V.; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh (2017)
In this paper, a numerical study on thermal postbuckling behavior of orthotropic circular plates is presented. The numerical solutions developed in this study are based on von Kàrmàn nonlinear strain - displacement relations. The governing nonlinear differential equations are transformed into linear differential equations. Both simply supported and clamped boundary conditions are considered. The radial edge load of circular plates is evaluated by assuming suitable admissible function for the lateral displacement. The postbuckling loads of orthotropic circular plates are evaluated using the determined linear buckling load and radial edge load. The numerical results obtained from the present investigation are compared with the known results reported in the literature and found in good agreement. The error percentage of the results has been predicted and a maximum error is found out to be 1.37 % for simply supported and 3.08 % for clamped boundary conditions respectively.